Motivation vs Remotivation as a Source of Ethnocultural Information (Based on Place Names of Karelia) - Irma I. Mullonen (Вопросы Ономастики, 2019)
The article analyzes the correlation between remotivation a toponym acquires in the course of its existence and its initial motivation, as well as the ways these processes reflect the ethnolinguistic, historical, and cultural contexts they were driven by. The lost original motivations have been restored for a number of toponymic stems, which rooted in the object’s inherent physical traits that mattered for the nominator. The process of place name rethinking by local people is most systemically manifested in toponymic legends. Thereby, the author distinguishes three cases illustrating the key interaction strategies for the linkages between the motivational meanings of place names and folklore pieces. The first one occurs in legends about primary inhabitants, which generally proceed from the same motifs that are engraved on in the primary place name, but capture the historical memory through the prism of mythological interpretation. The second one applies where the true sources of the name are undetectable, and a ready-made folklore motif is used to interpret the place name. This strategy is studied using the material of three Karelian toponymic stems with ‘female’-related meanings: Neičyt- / Neicyt- / Neitsyt- ‘maiden’s,’ Akka- : Akan- ‘mature woman’s,’ Nainen : Nais(en)- ‘woman’s, female,’ whose primary toponymic motivation is blurred. The third case is where motivation rethinking results in a replacement of the toponymic stem for a different one, which sounds similarly, but is driven by a folklore plot. As a result, the folklore text and the place name carry fundamentally different information. In Central Karelia, the islands traditionally used for drying fishing nets have turned into “treasure islands,” and the toponymic stem Uarto- : Uarro- ‘net drying stands’ acquired the form Uarreh- : Uartehe- ‘treasure, hoard,’ due to its folklore rethinking. The article shows that legend plots allude to the borderland position of Karelia, which refers to the area of Russian motifs or motifs associated with rethinking the ...